2020
DOI: 10.1002/pits.22356
|View full text |Cite
|
Sign up to set email alerts
|

Teacher training in K–12 student mental health: A systematic review

Abstract: Teachers are in a unique position to identify and support students who experience mental health concerns. The purpose of this systematic review was to (a) identify current available evidence‐based teacher training programs related to students' mental health, (b) review the content and delivery methods of the training, and (c) evaluate the quality of the research designs and evaluation methods of the training. Most training programs are delivered face‐to‐face and include interactive discussion and content knowl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 31 publications
0
32
0
Order By: Relevance
“…Similarly, Yamaguchi et al [19] noted that while most programs observed an improvement in knowledge, attitudes, confidence, and behavior, the quality of studies was low [19]. These findings were further confirmed by Ohrt et al [20]. Taken together, these reviews suggest that a focus on mental health literacy alone is unlikely to elicit behavior change.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Similarly, Yamaguchi et al [19] noted that while most programs observed an improvement in knowledge, attitudes, confidence, and behavior, the quality of studies was low [19]. These findings were further confirmed by Ohrt et al [20]. Taken together, these reviews suggest that a focus on mental health literacy alone is unlikely to elicit behavior change.…”
Section: Introductionmentioning
confidence: 90%
“…Three recent systematic reviews on youth mental health training for secondary school teachers have indicated a lack of evidence-based programs [18][19][20]. Anderson et al [18] found that only 6 programs had been evaluated, and while all improved the mental health knowledge of the participating teachers, none increased actual helping behavior toward students (eg, referring or recommending a student seek professional help).…”
Section: Introductionmentioning
confidence: 99%
“…Like several general and special education teachers in our sample, teachers report they do not have adequate levels of knowledge to support the mental health needs of students (Walter et al, 2006) yet have a strong desire to learn more. When Ohrt et al (2020) conducted a systematic review of the literature from over 100 years, they only found a meager 15 articles that “consisted of intervention studies focused on improving K–12 teachers' abilities to identify and manage student mental health concerns conducted either through a control group comparison or a pre/posttest evaluation” (p. 835). Their findings and those of this study clearly support the need to research more specific training programs related to enhancing teachers' knowledge of student mental health.…”
Section: Discussion and Implications For Practicementioning
confidence: 99%
“…Teacher training and awareness raising are common whole-school intervention approaches. A review summarized the effects of teacher training programs that aimed to increase teachers’ competence in addressing students’ mental health needs [ 34 ]. Most of the reviewed studies were successful in increasing knowledge among teachers and some also found improvement in teachers’ ability to intervene and refer students to appropriate services.…”
Section: Effectiveness Of Psychosocial School Interventionsmentioning
confidence: 99%